2011
DOI: 10.1002/jclp.20845
|View full text |Cite
|
Sign up to set email alerts
|

Insomnia as predictor versus outcome of PTSD and depression among Iraq combat veterans

Abstract: Results support the role of insomnia in the development of additional psychological problems and highlight the clinical implications for combat veterans, to include the importance of longitudinal assessment and monitoring of sleep disturbances, and the need for early intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
160
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(171 citation statements)
references
References 85 publications
(56 reference statements)
10
160
1
Order By: Relevance
“…The demoralization model suggests that PTSD symptoms are the causes of depressive symptoms (Mangelli et al, 2005). The synchronous change model suggests that PTSD and depression may be influenced by a third variable and show no real association with each other (Breslau & Schultz, 2013; Vinck, Pham, Stover, & Weinstein, 2007; Wright et al, 2011). In a twin study of 6609 members of the Vietnam Era Twin Registry (male–male twins), no residual genetic and environmental variance overlapped between combat exposure and major depression after controlling for variance common to PTSD (Scherrer et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The demoralization model suggests that PTSD symptoms are the causes of depressive symptoms (Mangelli et al, 2005). The synchronous change model suggests that PTSD and depression may be influenced by a third variable and show no real association with each other (Breslau & Schultz, 2013; Vinck, Pham, Stover, & Weinstein, 2007; Wright et al, 2011). In a twin study of 6609 members of the Vietnam Era Twin Registry (male–male twins), no residual genetic and environmental variance overlapped between combat exposure and major depression after controlling for variance common to PTSD (Scherrer et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…It is important to identify and address risk factors for worse sleep in veterans, given evidence that in addition to being a commonly reported symptom, 8 sleep has been shown to predict future psychopathology. 14,15 Thus, targeting sleep in veterans can improve current symptomatology (for those who have it), in addition to helping prevent the development of future psychiatric disorders. Additional research into risk and protective factors for sleep in OEF/OIF/OND veterans is warranted to better treat this population.…”
Section: Discussionmentioning
confidence: 99%
“…13 Further, recent evidence suggests that sleep disturbances may influence the development and course of subsequent psychopathology (e.g., depression, PTSD). 14,15 Fragmentation in rapid eye movement sleep specifically is predictive of PTSD. [16][17][18] Numerous studies have been conducted to identify correlates of sleep disturbance in veteran samples, 5,7 yet few have incorporated a three-group design that separates "true" controls from trauma-exposed controls and individuals with PTSD.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between sleep disturbance and PTSSs may be bi-directional. It was shown that exposure to trauma may cause sleep disturbance (Babson & Feldner, 2010), but insomnia and nightmares are also associated with an increased risk for onset and continuance of PTSD (Wright, Britt, Bliese, Adler, Picchioni, & Moore, 2011), so they may serve as risk factors for PTSSs. In general, the high positive correlations between GHQ-28 dimensions and PTSSs confirmed in our study among patients with gynaecological pathology are in line with the results of previous studies (Chung et al, 2002;Taubman-Ben-Ari et al, 2001).…”
Section: Discussionmentioning
confidence: 99%